Impact of Fintech on Financial Inclusion: The Mediating Role of Digital Financial Literacy: https://doi.org/10.55966/assaj.2025.4.1.068 - Hamza Khatri (Corresponding Author); Muhammad Abdullah Idrees; Farzeen Sultan (`, 2025)
This study examines the influence of Fintech on financial inclusion, particularly in developing economies, and explores the mediating role of digital financial literacy (DFL). By leveraging the Technology Acceptance Model (TAM), the research analyses how Fintech innovations such as mobile payments, digital wallets, and peer-to-peer lending can enhance access to financial services among marginalized populations. A structured questionnaire was administered to 153 respondents, and the data were analysed using Structural Equation Modelling (SEM). Findings reveal that Fintech significantly improves financial inclusion both directly and indirectly through digital literacy. Digital literacy was found to be a crucial enabler, allowing users to better understand and utilize digital financial platforms. The study highlights the need for targeted policies, regulatory support, and educational initiatives to maximize Fintech's potential. Theoretical and practical implications suggest that bridging digital gaps can contribute to equitable financial growth and economic empowerment, particularly in underserved communities. Keywords: Fintech, Financial Inclusion, Digital Financial Literacy, Technology Acceptance Model (TAM)